Young landscape architects' perceptions for Malaysian recreational forests - Hussein, Mohd Kher; Saidon, Mohd Nazri (Universiti Putra Malaysia Press, 2018)
The beauty of Malaysia’s recreational forests depends on the quality of their natural landscapes. These include flora and fauna, soil, topography/landform, geological features, and water bodies. Man-made elements such as bridges, litter bins, walkways, playground equipment, and shelters also contribute to the forests’ landscape beauty. Natural assets and man-made elements need to be in harmony with one another to maintain the visual attractiveness of these forests. However, there have been few studies on young landscape architects perceptions of Malaysia’s recreational forests. This study aimed at understanding this group of professionals’ perceptions of recreational forests and their site development in Malaysia. Two recreational forest sites were selected for this study. They are Sg. Chongkak Recreational Forest and the Ampang Recreational Forest in Selangor. A survey was conducted using photo-questionnaires with photographs as surrogates of the actual environment. A total of 119 young landscape architects participated in this study. Results showed that these young landscape architects perceived the natural landscapes of both parks as decent but the man-made facilities in both forests did not harmonize well with the existing natural surroundings. The findings in a form park management with regards to managing the beauty of recreational forests and efforts should be geared towards appreciating their aesthetic values, the architecture, and the overall ecology of these recreational forests.